Occurrence of campylobacter spp. and their antibiotic resistance profiles in cattle and farm environment - Aung, Wint Wint (2014)
Campylobacter, principally C. jejuni and C. coli, have been recognizedas one of the important causal agents of gastrointestinal infections in humans all over the world. The major source of human infection is raw or undercooked poultry meat but beef,pork, raw milk and water have also been associated with the infection. Most of the studies in Malaysia were on poultry and poultry products. The work on occurrence of Campylobacter in cattle, beef and milk is very scarce. Thus, the objectives of this study were to determine the occurrence of Campylobacter in cattle, farm environment, milk and meat,to identify the Campylobacter isolates by phenotypic method and multiplex PCR assay and to study the antibiotic resistance patterns of the isolates. One hundred and eighty (180) rectal swab samples from cattle, 68 samples from cattle farm environments, 36 raw milk samples from six farms and 30 beef samples from four markets were collected. All samples were cultured on selective media and isolated Campylobacter species were confirmed and identified using multiplex PCR. The overall prevalence of Campylobacter in dairy and beef cattle was 47 (26.1%) out of 180 samples. Eleven cattle were colonized by two Campylobacter species. The prevalence was higher in beef cattle 18 out of 57 samples (31.6%) compared to dairy cattle 29 out of 123 samples (23.6%) but the difference was not significant (p=0.256). The prevalence was significantly higher in calves 16 out of 40 samples (40%) than adult cattle 31 out of 140 samples (22.1%) (p=0.023). The isolation of Campylobacter from cattle was more at incubation temperature of 42˚C (25.0%) compared to at 37˚C (21.1%), however the difference was not significant (p=0.381) and kappa test statistic showed almost perfect agreement between the two different temperatures (kappa>0.8). Six Campylobacter species were identified at both temperatures; the most frequent isolated species was C. jejuni23 (39.6%) and followed by C. fetus13 (22.4%), C. upsaliensis8 (13.8%), C.coli5 (8.6%),C.hyointestinalis subsp. hyointestinalis 4 (6.9%) and the least prevalent species was C. lari3 (5.2%). However, two isolates were unidentified Campylobacter species. From a total of 68 environmental samples, 19 27.9%)Campylobacter isolates were isolated, namely from 10 out of 27 water samples (37.0%), four out of 16 flies samples (25.0%), one out of seven feed samples (14.3%), three out of nine floors of the cattle houses samples (33.3%) and one out of nine water trough samples (11.1%) which are considered as the risk factors for Campylobacter in cattle. Flies could be an essential vector for transmission of Campylobacter from contaminated environment to cattle in the farms or from infected animals to the environment. The occurrence of Campylobacter in feed, floor, drinking water and water trough could be contaminated via flies and animal faeces.Ten (10) isolates (27.8%) of the 36 raw milk samples were Campylobacter positive, however none of the 30 retail beef samples were positive. The occurrence of Campylobacter in milk could have resulted from contamination during milking. The absence of Campylobacter in retail beef probably suggests they were not contaminated at processing and poor resistance of Campylobacterto atmospheric oxygen and other environmental pressures during storage, transportation and retailing may cause Campylobacter to convert to viable but non culturable (VBNC) form.The overall isolation rate of Campylobacter from cattle, environment samples, beef and milk when incubated under two different temperatures was higher at 42˚C (22.6%) when compared to 37˚C (18.5%); however,the difference was not significant (p=0.199) and kappa test statistic showed good agreement between the two different incubation temperatures (0.6≤k<0.8) and six Campylobacter species were isolated at both temperatures. The Campylobacter isolates were tested for antibiotic resistance using standard disc diffusion method and Minimum Inhibitory Concentration (M.I.C) method. The Campylobacter isolates were tested against 12 antibiotics and showed resistance to clindamycin and nalidixic acid (50.9%) each, cefotaxime (49.1%), sulfamethoxazoletrimethoprim (40%), ampicillin (38.2%), ciprofloxacin (23.6%), enrofloxacin and streptomycin (21.8%), tetracycline (20%), erythromycin (18.2%), chloramphenicol (16.4%) and gentamicin (12.7%) by disc diffusion method. For M.I.C method using M.I.C.Evaluator strips, the isolates were tested against four antibiotics. The isolates were found resistant to ampicillin and tetracycline (26.3%), ciprofloxacin (21%) and erythromycin (15.8%). All the isolated Campylobacter spp. in this study were resistant to five antibiotics namely ampicillin, clindamycin, nalidixic acid, streptomycin and cefotaxime. The resistance rates between the two methods for four antibiotics were found comparable. There is almost perfect agreement of kappa test statistic for ampicillin, erythromycin and ciprofloxacin (kappa>0.8) and also good agreement for tetracycline (0.6≤k<0.8) between both methods. Multidrug resistance, that is resistant to three or more antibiotic classes, was high, at 52.7%. Multidrug resistant Campylobacter isolates poses a significant risk if they are resistant to the drugs of choice and alternative drugs for treatment. It can be concluded from this study that Campylobacter species are quite prevalent at 26.1% in cattle in the farms. The presence of Campylobacter in cattle and milk could be a potential source of human infections and environmental contamination. Hence, it is recommended that good animal husbandry practices (GAHP) and good milking procedures must be practiced at the farms and good manufacturing procedures (GMP) at abattoirs where it may reduce the risk to humans through meat, milk and environment. The use of antibiotics in animals should also be controlled and monitored to reduce antibiotic resistance.